Effect of recombination and binding properties on the performance of dye sensitized solar cells based on propeller shaped triphenylamine dyes with multiple binding groups. (February 2016) - Vinayak, Manikkedath V.; Lakshmykanth, Thyagarajan M.; Yoosuf, Muhammed; Soman, Suraj; Gopidas, Karical R.
Graphical abstract: Highlights: Three novel Triphenylamine based dyes having phenyethynyl π-bridges reported. Optical properties studied and HOMO–LUMO energy levels determined. DSSC fabricated with the best performing dye showed 5.05% efficiency. Low efficiency for other dyes attributed to low electron lifetime. Orientation of dyes on TiO2 surface contributes significantly towards efficiency. Abstract: Herein we report three novel donor-π-acceptor type dyes TPAA1, TPAA2 and TPAA3, which were investigated for photophysical and electrochemical properties as well as dye-sensitized solar cell performance. These dyes have triphenylamine group at the core of the structure acting as the donor moiety which is radially connected to one, two or three cyanoacrylic acid acceptor groups through phenylethynyl bridges. These dyes can harvest light up to 600 nm as revealed by absorption studies, which is complemented by the IPCE spectra. The propeller shapes of the dyes prevent their aggregation on TiO2 surface and give better solar cell performance without the need for any co-adsorbent. DSSCs fabricated using TPAA1 gave the best solar cell performance with a short circuit current ( J sc ) of 9.96 mA cm −2, an open circuit voltage ( V oc ) of 0.69 V and a fill factor (FF) of 0.73, which correspond to an overall power conversion efficiency of 5.05%. Infrared spectroscopy and computational studies were carried out which gave interesting insights into the mode of dye binding to TiO2 . Lifetime and recombination measurements were carried out using charge extraction and detailed impedance analysis. The Nyquist and Bode plots along with the fitted EIS data reveal that resistance to recombination is higher for TPAA1 in comparison to TPAA2 and TPAA3 leading to better cell performance, which in turn may be attributed to the orientation of the dye molecule on the TiO2 surface.